Legitimizers of violence in heterosexual couples, taking into account gender as a social practice structure - Angélica Orozco; Aura Aguilar; María Amarís (Saúde e Sociedade, 2021)
This study aimed to show the social representations related to female victims, aggressors and services providers as great legitimizers of violence against women, considering their gender and social practice in Barranquilla, Colombia. This is a qualitative research, with a phenomenologicalhermeneutic approach and the theory of social representations, which used in depth interviews and content analysis as data collection technique. Findings suggest violence used to regulate behavior, passionate jealousy, conciliatory strategies and the assumed women satisfaction are legal means of violence in heterosexual couples. We conclude this type of violence has been established due to social representations, stereotypes and beliefs that reinforce male dominance, especially over female sexuality and body as properties for their pleasure and forms of authority, power, control and inequality, which are imposed by the patriarchal model.